On the Issue of Synchronization of Real and Virtual Processes in the Context of the Evolution of the Modern Information Society - Yablochnikov, S. L.; Yablochnikova, I. O.; Kuptsov, M. I.; Machiboroda, M. N.; Bondarenko, I. V. (2021 Systems of Signal Synchronization, Generating and Processing in Telecommunications (SYNCHROINFO, 2021)
In the context of the functioning and evolution of the modern information society, the processes that are actually implemented in the economy, public life, and even politics, in a certain way significantly correlate with the totality of information processes in numerous social networks. Individuals and legal entities, business structures and non-profit organizations, social movements and political parties create multimedia content and post it on social networks, contributing to its active promotion in the virtual world. Various principles, methods and tools are used by the owners of such content to generate active interest in information resources posted on social networks and attract new users. The purpose of such actions is to activate and optimize their real activities, regardless of the sphere of interests. In the article, the authors analyzed a number of aspects that indicate the synchronization of real and virtual processes. Such conclusions were made based on the analysis and processing of a significant amount of statistical information about the functioning of several specific groups of accounts in social networks, in particular in the VKONTAKTE network. A number of models are proposed that allow predicting the implementation of information processes in social networks in the short and medium term and their synchronization with real processes.